Politics of Memory: Digital Repositories, Settler Colonialism, and Jordan Abel's Un/inhabited. - Schmaltz, Eric (English Studies in Canada, 2019)
A literary criticism of the book "Un/inhabited" by Jordan Abel is presented. Topics discussed include relevance of the poetry of Nisga'a writer and scholar Abel to the discussions related to the politics of memory, and examination on Abel's digital poetry as a form of digital activism that intervenes into the relationship between online textual repositories, the politics of memory, and settler colonialism.